2014
DOI: 10.1088/0256-307x/31/1/017401
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of High-Temperature Superconductivity in One-Unit-Cell FeSe Films

Abstract: Heterostructure based interface engineering has been proved an effective method for finding new superconducting systems and raising superconductivity transition temperature (T C ) 1-7 . In previous work on one unit-cell (UC) thick FeSe films on SrTiO 3 (STO) substrate, a superconducting-like energy gap as large as 20 meV 8 , was revealed by in situ scanning tunneling microscopy/spectroscopy (STM/STS). Angle resolved photoemission spectroscopy (ARPES) further revealed a nearly isotropic gap of above 15 meV, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
264
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 288 publications
(286 citation statements)
references
References 20 publications
14
264
3
5
Order By: Relevance
“…Ex situ transport measurements of single-layer FeSe films (SLFs) grown on SrTiO 3 substrates (referred as FeSe S hereafter) with capping layers show an onset T c of B40 K (ref. 4), much higher than the 8 K bulk value. Although the true T c of FeSe S remains to be confirmed by in situ transport measurements, in situ angle-resolved photoemission spectroscopy (ARPES) studies found a T g B65 K (refs 5,6).…”
mentioning
confidence: 68%
“…Ex situ transport measurements of single-layer FeSe films (SLFs) grown on SrTiO 3 substrates (referred as FeSe S hereafter) with capping layers show an onset T c of B40 K (ref. 4), much higher than the 8 K bulk value. Although the true T c of FeSe S remains to be confirmed by in situ transport measurements, in situ angle-resolved photoemission spectroscopy (ARPES) studies found a T g B65 K (refs 5,6).…”
mentioning
confidence: 68%
“…An ex situ transport measurements performed on FeSe/STO protected by multiple layers of FeTe and amorphous Si overlay revealed a zero-resistance T c of 23.5 K and an onset T c > 40 K (ref. 15). Evidently the addition of protection layers suppresses superconductivity in single-layer FeSe.…”
mentioning
confidence: 99%
“…By introducing impurity atoms onto the sample, we show that the magnetic impurities (Cr, Mn) can locally suppress the superconductivity but the non-magnetic impurities (Zn, Ag and K) cannot. Our results indicate that single-layer FeSe/ SrTiO3 has a plain s-wave paring symmetry whose order parameter has the same phase on all Fermi surface sections.Recently the discovery of enhanced superconductivity in single-layer FeSe on SrTiO3(001) has attracted tremendous interest [1][2][3][4][5][6][7][8][9], not only for the new possible superconducting transition temperature records of Fe-based superconductors and interfacial superconductors (65K [3,4] or even higher [9]), but also its intriguing mechanism that enhances the paring. Thus it is of great importance to understand the pairing symmetry and underlying electron structure of single-layer FeSe/SrTiO3(001).…”
mentioning
confidence: 99%